Dehydroepiandrosterone (DHEA) reduces neuronal injury in a rat model of global cerebral ischemia. - Li, H; Klein, G; Sun, P; Buchan, A (2001)
INTRODUCTION: Many studies report an inverse correlation between levels of DHEA and neurological diseases. Exogenous DHEA protects hippocampal neurons against excitatory amino acid induced neurotoxicity. The purpose of this experiment is to evaluate the effect of DHEA in an animal model of transient but severe forebrain ischemia. METHODS: At thirteen days prior to induction of ischemia, male Wistar rats were implanted with various doses of DHEA-placebo, 25 mg, 50 mg or 100 mg. Forebrain ischemia was induced for 10 min using a modified four-vessel occlusion technique, with hippocampal neuronal injury assessed at 7 days post-ischemically and expressed as a percentage of total cells. RESULTS: Both normal and necrotic hippocampal CA(1) cells were counted. Percentages of hippocampal injury observed were 88+/-13% in animals treated with placebo, 84+/-8% in the 25 mg DHEA group, and 60+/-7% in the 50 mg DHEA group. Animals treated with 100 mg DHEA displayed a significant (P<0.05) reduction of hippocampal CA(1) cell injury at 60+/-7% CONCLUSION: Treatment with a high dose, but not a low or moderate dose, of DHEA implantation reduces hippocampal CA(1) neuronal injury following severe but transient forebrain ischemia.